Virtual Ethnography: Interactive Interviewing Online as Method - Susan Crichton; Shelley Kinash (The Canadian Network for Innovation in Education (CNIE), 2008)
Recognizing the power of the Internet to connect people, regardless of place or time, we explore the notion of a virtual form of ethnography, suggesting online, textual interactive interviews are worthy of research consideration. This paper reports on three research projects, drawing examples from almost ten years in the evolution of Internet supported conferencing software. It is the position of this paper that we were able to share and develop new insights into being authors, interlocutors, online learners, online researchers, and members of an educational context. Further, we feel that we were able to sustain conversations beyond the scope of many traditional face-to-face interview sessions, noting that the participants enjoyed the process and often found it hard to quit their interactions with us. Hence our position that even though the technology is still emerging and improving, the potential is clearly rich, inviting, and worth continued study.nstructor if given the authority in a social constructivist learning environment.